Recurrence of Retinopathy of Prematurity in Zone II Stage 3+ after Ranibizumab Treatment: A Retrospective Study - Qinrui Hu; Yujing Bai; Xiaoli Chen; Lvzhen Huang; Yi Chen; Xiaoxin Li (Journal of Ophthalmology)
Objective. To determine the prevalence and risk factors for the recurrence of retinopathy of prematurity (ROP) in Zone II Stage 3+ after ranibizumab treatment. Methods. This was a retrospective, nonrandomized, noncontrolled study that excluded Zone I and aggressive posterior ROP (APROP) cases. Infants who developed Zone II Stage 3 ROP with plus disease and underwent initial intravitreal injection of ranibizumab (IVR) were recruited. Patients were divided into 2 groups based on the outcome after initial ranibizumab treatment: recurrence of ROP or favorable outcome. Data was collected and analyzed by SPSS 16.0. Results. Forty-two patients were included, and 80 eyes with Zone II Stage 3+ were subjected to IVR treatment. Eleven of 42 patients (26.2%, 18 eyes) had a recurrence of ROP after the initial treatment. On univariate analysis, preretinal hemorrhage before treatment was significantly different between the two groups (P=0.000). Multivariate analysis found that preretinal hemorrhage before treatment was the only factor associated with the recurrence of ROP in our study (P=0.004). Conclusions. The recurrence rate of ROP in Zone II Stage 3+ after initial ranibizumab treatment was notable and preretinal hemorrhage before treatment was associated with the recurrence of ROP in our study.